PEMBELAJARAN BERBASIS PROYEK MENINGKATKAN KETERAMPILAN KOLABORATIF SISWA DI SD NEGERI BONIPOI 2 - Bayu A. Saputra Adu; Lero, Merlinda Gadi; Djabi, Joi Enjelika; Leltakaeb, Florida Ester; Talan, Yornalince; Betty, Ingrit; Mbuik, Heryon Bernard (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low collaborative skills of elementary school students, as indicated by the lack of active participation in group work, ineffective communication, and unequal responsibility in completing group assignments. The purpose of this study was to determine the effectiveness of implementing the Project Based Learning (PjBL) model in improving the collaborative skills of fifth-grade students at SD Negeri Bonipoi 2. This study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The research subjects were fifth-grade students of SD Negeri Bonipoi 2. Data on collaborative skills were collected through observation using a collaborative skills assessment sheet that included aspects of teamwork, communication, responsibility, active participation, and respect for others’ opinions. The data were analyzed using descriptive analysis and an improvement test based on pretest and posttest results. The findings revealed that the implementation of the PjBL model improved students’ collaborative skills. This improvement was reflected in students’ increased ability to cooperate, discuss, share tasks, respect group members’ opinions, and take responsibility for completing projects. Therefore, the Project Based Learning model is effective as an alternative instructional model to enhance collaborative skills among elementary school students.